Filme de partículas de cálcio promove fotoproteção e economia de água na videira (Vitis labrusca L.) - Barbosa, Nadja Tamires Borges (2020)
Grape growing has expanded considerably in the Northeast region of Brazil in recent years. However, due to climate changes, such as low rainfall amounts, high irradiance, and high evaporative demand, the effects of abiotic stress on plant performance have intensified. To mitigate this serious situation in agriculture, the technology of particle films has been recognized as a promising strategy for sustainable relief from abiotic stress and adverse conditions in grape growing. Thus, the aim of this study was to investigate the effects of application of calcium particle film on the growth of the cv. Isabel Precoce to evaluate the physiological and agronomic performance of plants subjected to different water regimes under summer conditions in the Northeast of Brazil. The experiment was conducted in the experimental area of the Universidade Federal de Sergipe and comprised four treatments: i) 65% of the crop evapotranspiration (ETc) with calcium particle film (CaO 7%); ii) 65% of the ETc under full sun; iii) 100% of the ETc with calcium particle film; and iv) 100% of the ETc under full sun (n = 4), applied from the fruit development phenological stage until harvest. The following parameters were evaluated: leaf water potential, gas exchanges, relative water content, chlorophyll a fluorescence transient, Falker chlorophyll indices, lightness, total soluble solids, pH, total acidity, berry firmness, and grapevine yield. The calcium particle film provided shading effects on the leaves, photoprotection, and increases in chlorophyll indexes. The emission of the OJIP curve declined in the grapevines with film, improving the energetic metabolism of the photosynthesis and providing greater efficiency of the electron flows energized by the photosystems and by the electron transport chain, especially at the time of greatest solar radiation. Water potential and yield increased in the plants treated with film, especially prominent were water savings of up to 35% for the plants with 65% of ETc with film. Increases were also found in photosynthetic rate (A) and reductions in stomatal conductance (gs) and transpiration rate (E), improving water use efficiency and physiological performance in the grapevines treated with film. These results are shown by the relative water content, in which the treatments with film were able to reduce water loss in the grapevine leaf tissues. Even with reduction in water supply to the plants, the film maintained the physical-chemical characteristics of grapes and increased yield. Thus, calcium particle film and a lower water regime can be recommended as an effective alternative for sustainable grape growing, mitigating the effects of climate changes on grapevines.